STUDI LITERATUR: ANALISIS HUBUNGAN DAN PENGARUH LINGKUNGAN BELAJAR TERHADAP MOTIVASI BELAJAR, RESILIENSI MATEMATIS, DAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Alvi Hidayatusholihah; Taufik Muhtarom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship and influence of the learning environment on learning motivation, mathematical resilience, and mathematics learning outcomes of elementary school students. This research method uses a literature study method by reviewing 43 relevant journal articles published between 2020-2025. Data collection techniques are carried out through the Google Scholar database using specific keywords. The article selection process is carried out through the process stages, include, exclude. Includes: (1) researchers enter the keyword "Learning Environment" then there are 2,530,000 articles. (2) researchers filter articles by adding the keyword "Elementary School" there are 1,790,000 articles. (3) researchers add the keywords "Learning Motivation, Mathematical Resilience, and Learning Outcomes" there are 2,260. (4) researchers adjust journals that are relevant to the research title and get 1,010. (5) then researchers filter based on the abstract to get 125 articles. (6) researchers download articles that can be opened and the suitability of the title and research subject, namely 43 articles. Data analysis was conducted through four stages, namely: (1) source collection, namely the identification and downloading of 43 relevant articles through the systematic procedures that have been explained; (2) source criticism, namely the assessment of the authenticity and accuracy of the article content through internal criticism that includes a review of the author's credibility, journal reputation, and the suitability of the content to the research focus; (3) interpretation, namely the interpretation of facts obtained from the literature within the framework of reconstructing findings to form factual and logical values ​​and meanings; (4) historiography, namely the systematic preparation of research reports in accordance with applicable scientific provisions. Data validity is guaranteed through source triangulation, member checking by fellow researchers, and reference source validation sheets that have been validated by expert lecturers.The results of the study indicate that the learning environment has a significant relationship and influence on these variables. A conducive learning environment provides stimulation that can increase student engagement, while emotional support can help strengthen student resilience in facing math difficulties. The results of this study indicate that the school environment, such as classroom climate and supportive social interactions (non-physical environment), has a more significant influence than the family and community environment in improving students' mathematics learning outcomes. This study concludes that structuring the learning environment is a key factor in optimizing the mathematical achievement of the remainder of elementary school.